2018
DOI: 10.3310/eme05050
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal aflibercept compared with panretinal photocoagulation for proliferative diabetic retinopathy: the CLARITY non-inferiority RCT

Abstract: Background Panretinal photocoagulation (PRP) has been the standard of care for patients with proliferative diabetic retinopathy (PDR) for the last 40 years. It prevents severe visual loss in PDR but is also associated with adverse effects on visual functions. Objectives The clinical efficacy and mechanistic evaluation of aflibercept for proliferative diabetic retinopathy (CLARITY) trial evaluated the clinical efficacy, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…19 Indeed, anti-VEGF therapy is now a recognized treatment for diabetic macular edema; it can significantly inhibit the growth of new blood vessels, reduce edema, and eventually improve vision. 1618 Our results demonstrated improvements in BCVA and CFT after aflibercept treatment, in agreement with the findings of the CLARITY trial that compared aflibercept with pan-retinal photocoagulation; 20,25,26 our results are also consistent with the findings of a phase IV study in which a treat-and-extend regimen of aflibercept was found to improve visual acuity and retinal edema in eyes with Type 3 neovascularization, with good tolerability over 52 weeks. 27 Previous studies showed that when an anti-VEGF treatment was administered to patients with retinal venous obstruction, the anti-VEGF group displayed delayed progression of non-perfusion areas and showed improved reperfusion, compared with the control group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…19 Indeed, anti-VEGF therapy is now a recognized treatment for diabetic macular edema; it can significantly inhibit the growth of new blood vessels, reduce edema, and eventually improve vision. 1618 Our results demonstrated improvements in BCVA and CFT after aflibercept treatment, in agreement with the findings of the CLARITY trial that compared aflibercept with pan-retinal photocoagulation; 20,25,26 our results are also consistent with the findings of a phase IV study in which a treat-and-extend regimen of aflibercept was found to improve visual acuity and retinal edema in eyes with Type 3 neovascularization, with good tolerability over 52 weeks. 27 Previous studies showed that when an anti-VEGF treatment was administered to patients with retinal venous obstruction, the anti-VEGF group displayed delayed progression of non-perfusion areas and showed improved reperfusion, compared with the control group.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the intravitreal injection of anti-VEGF agents (e.g., ranibizumab) is sufficient for management of DR. 1618 Intravitreal injection of ranibizumab causes reperfusion in ischemic regions of the retina, suggesting that DR may be reversed after treatment with ranibizumab; 19 however, this hypothesis has not been fully tested for other anti-VEGF agents. The CLARITY non-inferiority trial showed that aflibercept is an effective alternative for patients with proliferative DR. 20 Aflibercept is a human recombinant fusion protein 21 that acts as a high-affinity soluble decoy receptor for VEGF and placental growth factor. 22 In the context of DR, VEGF activation enhances endothelial cell permeability, proliferation, survival, and migration.…”
Section: Introductionmentioning
confidence: 99%
“…50% of PDR patients who do not receive timely treatment develop serious vision loss within 5 years [3]. Sivaprasad et al, [13] studied the effect of repeated aflibercept injection in comparison to standard PRP in cases of PDR without VH and showed that regression of retinal neovascularization at 2 years was seen in 81% of aflibercept-treated eyes and 78% of PRP-treated eyes. 64% of aflibercepttreated eyes had total regression of neovascularization, compared to 34% in PRP eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating anti-VEGF therapy for proliferative diabetic retinopathy (PDR) were initially promising for a move away from pan retinal photocoagulation (PRP). 51 However, the longer term results were less supportive of intravitreal therapy, 52 and combined with financial and compliance concerns; 53 there has been variable uptake of this mode of therapy for PDR. However, with the potentially lower risk viral transmission via intravitreal compared to PRP (which takes a longer time to perform) may alter practices the face of this pandemic.…”
Section: Specific Considerationsmentioning
confidence: 99%